Efforts to Improve Athletic Achievement in Short Distance Running by Providing Strengthening to Class X Students of TKI 1 SMK Negeri 2 Majene - Burhanuddin, Sudirman; Bachtiar, Ishak; Fahrizal, Fahrizal (SHOOTING: Journal of Sport, Health, and Education, 2024)
The problems to be studied in this research are: (a) How can you improve your ability to run short distances by applying reinforcement? (b) What is the effect of strengthening on short distance running? The aim of this research is (a) to find out how to increase short distance running ability by applying reinforcement. This research uses two rounds of action research. Each round consists of two stages, namely: design, activities and observations. Reflection and revision The target of this research is Class From the results of the analysis, it was found that student learning achievement increased from cycles I to III, namely, cycle I (62%), cycle II (74%) and cycle III (91%). The conclusion of this research is that providing reinforcement can influence the short distance running ability of class X TKJ 1 students at SMK Negeri 2 Majene and the learning model can be used as an alternative in the PJOK learning process.